NILAVAAGAI CHOORANAM – A SIDDHA HERBAL MEDICINE - Asokan, Raga vanee; Kabilan Natarajan, (International Journal of Ayurveda and Pharma Research, 2019)
Siddha system is mainly experienced in the Southern part of India. It is one of the most primitive traditional medicines in the world which treats not only the body but also the mind and the soul. The word Siddha derived from Tamil words Siddhi which means An object to be Attained or perfection or heavenly bliss. The aim of this review article is to explore the scientific literary evidences for the therapeutic usage of Nilavaagai chooranam for respiratory illness (Swasakasam, Iya noi) as mentioned in Siddha literature Siddha vaidaya Thirattu and to focus on the Pharmacological activity for the healing nature of the drug. Most of the raw drugs used for the preparation of Nilavaagai chooranam have Broncho dilatory activity, Anti-microbial activity, Anti-inflammatory activity, Immunomodulatory activity, Anti-histamine activity hence justifying its usage in respiratory ailments.